2002
DOI: 10.1002/1521-396x(200202)189:2<373::aid-pssa373>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

On the Structural and Magnetic Properties of R2Fe17?x(A,T)x (R = Rare Earth; A = Al, Si, Ga; T = Transition Metal) Compounds

Abstract: R 2 Fe 17 (R ¼ rare earth) intermetallic compounds constitute one of the most important classes of materials identified as high-energy permanent magnet materials. They crystallize either in the rhombohedral Th 2 Zn 17 structure (for light R) or in the hexagonal Th 2 Ni 17 structure (for heavy R). In this article, we discuss the variations in the lattice parameters (unit cell volume), site occupancies and Curie temperature when non-transition and transition metals are substituted for Fe in R 2 Fe 17 compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…R2Fe17 compounds were studied in late the 1970s and the values of (BH)max and Coercivity (Hc) were found about 26 MGOe and 15 kOe respectively but they have very low Curie temperature (~473 K for Gd2Fe17 and ~300 K for Dy2Fe17) and low magnetic anisotropies [1]. Many researches have been done to improve the curie temperatures of Dy2Fe17 [2][3][4] either by replacing the Fe atoms with non-magnetic atoms (Al, Si, Ga) [5] or by doping refractory atoms (Ti, V, Mo, Nb, W, Zr) in Fe site [6][7][8][9][10]. It is also found that substitution of magnetic atoms such as (Co, Ni, Cr, Mn, Ni) [11], non-metals such as C, N, and H in R2Fe17 lattice also increase the curie temperature of R2Fe17 compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R2Fe17 compounds were studied in late the 1970s and the values of (BH)max and Coercivity (Hc) were found about 26 MGOe and 15 kOe respectively but they have very low Curie temperature (~473 K for Gd2Fe17 and ~300 K for Dy2Fe17) and low magnetic anisotropies [1]. Many researches have been done to improve the curie temperatures of Dy2Fe17 [2][3][4] either by replacing the Fe atoms with non-magnetic atoms (Al, Si, Ga) [5] or by doping refractory atoms (Ti, V, Mo, Nb, W, Zr) in Fe site [6][7][8][9][10]. It is also found that substitution of magnetic atoms such as (Co, Ni, Cr, Mn, Ni) [11], non-metals such as C, N, and H in R2Fe17 lattice also increase the curie temperature of R2Fe17 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Betancourt et al (2003) [21] reported that Zr and Nb substitution can also improve magnetic properties. The curie temperatures of Ce2Fe17 [22], Gd2Fe17 [5] Dy2Fe17 [8], Pr2Fe17 [23], etc., are improved by the addition of elements like Si, Cr, Mn, and Ga. The substitution of the non-magnetic atom into the R2Fe17 brings the concomitant decrease in magnetization which affects the energy product of the permanent magnets [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, high level of substitution of non-magnetic atoms to maximum of 10 per formula unit in R 2 Fe 17 compound is possible [26][27][28]. However, earlier reports on Ga and Ti substitution in R 2 Fe 17 À x Mx compounds show substantial reduction in T c and magnetization [29,30] with high substitution content (x42). Thus in the present study the substitution of non-magnetic atoms was restricted to low levels (x r1).…”
Section: Introductionmentioning
confidence: 99%
“…Such properties depend mainly on the relative amounts of the different valance states of the doped TMI in the glass network [1][2][3]. When glasses are doped with two different TMI, their technological applications become of high interest.…”
Section: Introductionmentioning
confidence: 99%